Physical and mechanical parameters correlated to the ripening of mangoes (Mangifera indica L.) cv. 'Tommy Atkins' (2017)
Studies on the maturation of mangoes in growing regions may help determine the optimal harvest strategies to support proper post-harvest handling and improve the fruit shelf life. The aim of the present study is to evaluate changes and establish correlations of physical and mechanical parameters during the ripening of mangoes cv. 'Tommy Atkins' collected from fifty plant rows in a commercial orchard. The fruits were picked at 35, 50, 65, 80, 95, 110, 125 and 135 days after flowering (DAF). Fruit mass, longitudinal diameter (LD), transverse diameter (TD), fruit firmness, force and maximum deformation compression, tension and Hencky’s strain were evaluated. The statistical design was totally randomized with four replications with ten fruits each. The results were submitted to longitudinal data analysis due to the quantitative nature imposed by the harvest time factor. Hencky’s strain curves and deformity underwent an analysis of the standard error of the mean. From the beginning of the harvest up to 125 DAF, the fruit went through an increase in its mass, in its longitudinal and transverse diameters and in its compressive strength. Both physical and mechanical parameters exhibited high correlation, up 0.93, as regards the fruit maturation stages. This demonstrates that the mangoes cv. 'Tommy Atkins’ hold excellent prospects of development.